FAKTOR-FAKTOR YANG MEMPENGARUHI MARGIN PEMASARAN TERNAK SAPI POTONG DI KABUPATEN KUPANG - Ferdinan Suharjono Suek; Melkianus Dedimus Same Randu (Partner, 2018)
The research aim’s to find the factors which influence the marketing margins of beef cattle in Kupang Regency. The research was conducted using a survey method. The research involved 94 respondentsas samples, consisted of 76 breeders, 12 intermediary traders, and 6 inter-island traders. Respondents of breeders were determined by simple random sampling, while intermediatery traders and inter-island traders were determined by snowballs sampling. The research data were collectedthrough direct observation and interview that use questionnaires. The results showed that the equation model Y = - 27,804 + 3,10X1 + 0,158X2. The coefficient of determination (R2) of 0.909 given overview of marketing margins which could be explained together on 90.9% by marketing costs and sales volume. The results of marketing testing cost and partial sales volume or as a whole showed a very significant effect (P <0.01) on marketing margins. In conclusion, the increase of marketing costand sales volume had contribution toward the marketing margin of beef cattle in Kupang Regency.